If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 15 = 45 + 7x Reorder the terms: 15 + -3x = 45 + 7x Solving 15 + -3x = 45 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 15 + -3x + -7x = 45 + 7x + -7x Combine like terms: -3x + -7x = -10x 15 + -10x = 45 + 7x + -7x Combine like terms: 7x + -7x = 0 15 + -10x = 45 + 0 15 + -10x = 45 Add '-15' to each side of the equation. 15 + -15 + -10x = 45 + -15 Combine like terms: 15 + -15 = 0 0 + -10x = 45 + -15 -10x = 45 + -15 Combine like terms: 45 + -15 = 30 -10x = 30 Divide each side by '-10'. x = -3 Simplifying x = -3
| -2(x+13)-8=2 | | 2h^2+3h+4=0 | | 3(n-4)+5(6n-4)=7(n+6)-24 | | (3x^2)-7x-20= | | 12a^2+16ab-3b^2= | | 4/10=n/35 | | 2/20=3/m | | x^3-9x^2+15x+17= | | -12(n-1)=2(-12-2n)-5 | | (-9x)x(-7)=63x | | 27x^3+54x^2+36x=-8 | | 3(10+2m)=3(2m+5) | | 8x^3+36x^2+54x=-27 | | 24x+20y=750 | | n-(-7)=-3 | | (2x-3)*(2x+3)=-4 | | 3(8x+5)-19=7-3x | | 2lgx=lg(4x-3) | | 2x^2+27x-4.5=0 | | z+10=-6 | | 4p-25=-11+2p | | 0.25y-0.8=0.15Y+2-0.6y | | 0.1(0.1x+0.3)-0.6= | | 8x-82=-2 | | 40=9x-59 | | 3x+4x-15=35 | | 2x(5-3x)= | | 1.n=6 | | 2x+6=-2x+2 | | 3x+2=-6x-7 | | 13x-3=8x-9 | | 2x+12=-12-4x |